Microbial Activity Response to Solar Radiation across Contrasting Environmental Conditions in Salar de Huasco, Northern Chilean Altiplano - Hernández, Klaudia L.; Yannicelli, Beatriz; Olsen, Lasse M.; Dorador, Cristina; Menschel, Eduardo J.; Molina, Verónica; Remonsellez, Francisco; Hengst, Martha B.; Jeffrey, Wade H. (Frontiers in Microbiology, 2016)
In high altitude environments, extreme levels of solar radiation and important differences of ionic concentrations over narrow spatial scales may modulate microbial activity. In Salar de Huasco, a high-altitude wetland in the Andean mountains, the high diversity of microbial communities has been characterized and associated with strong environmental variability. Communities that differed in light history and environmental conditions, such as nutrient concentrations and salinity from different spatial locations, were assessed for bacterial secondary production (3H-leucine incorporation, BSP) response from short-term exposures to solar radiation. We sampled during austral spring seven stations categorized as: a) source stations, with recently emerged groundwater (no-previous solar exposure); b) stream running water stations; c) stations connected to source waters but far downstream from source points; and d) isolated ponds disconnected from ground sources or streams with a longer isolation and solar exposure history. Very high values of 0.25 µE m-2 s-1, 72 W m-2 and 12 Wm-2 were measured for PAR, UVA, and UVB incident solar radiation, respectively. The environmental factors measured formed two groups of stations reflected by PCA analyses (near to groundwater sources and isolated systems) where isolated ponds had the highest BSP and microbial abundance (35 microalgae taxa, picoeukaryotes, nanoflagellates and bacteria) plus higher salinities and PO43- concentrations. BSP short-term response (4 h) to solar radiation was measured by 3H-Leucine incorporation under four different solar conditions: full sun, no UVB, PAR, and dark. Microbial communities established in waters with the longest surface exposure (e.g. isolated ponds) had the lowest BSP response to solar radiation treatments, and thus were likely best adapted to solar radiation exposure contrary to ground source waters. These results support our light history (solar exposure) hypothesis where the more isolated the community is from ground water sources, the better adapted it is to solar radiation. We suggest that factors other than solar radiation (e.g., salinity, PO43-, NO3-) are also important in determining microbial productivity in heterogeneous environments such as the Salar de Huasco.